FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA AUDITOR DI ERA VOLATILITY, UNCERTAINTY, COMPLEXITY, DAN AMBIGUITY (VUCA) - Leriza Desitama Anggraini; R M Rum Hendarmin (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2023)
VUCA is a condition that affects the state of the economy because of the rapid changes in various sectors that create unexpected and difficult to predict business challenges where this era will test the viability of companies. Auditors have an important role in the survival of the company. The sustainability of the company can be realized, one of which is from financial reports that are presented fairly. Therefore, to encourage this success, the auditor needs good and quality performance. This study aims to analyze and examine the factors that can affect the performance of auditors in the KAP Palembang City. This research is included in the type of quantitative descriptive research. The processed data is primary data, where data is obtained through distributing questionnaires and direct interviews as a means of confirmation to informants. Objects in this study include role conflict, audit structure, motivation, audit fees and job satisfaction. The sample in this study is 40 auditors who have met the criteria. The results of the analysis and testing of data and hypotheses show that partially the role conflict variables, audit structure variables, and motivational variables do not affect the auditor's performance. Meanwhile, the variable audit fees and job satisfaction variables influence the auditor's performance. Furthermore, simultaneously, these variables affect the auditor's performance.